AKIBAT HUKUM TERHADAP ISTERI PERTAMA YANG PENCATATAN PERKAWINANNYA DILAKUKAN SETELAH PERKAWINAN KEDUA DALAM PERKAWINAN POLIGAMI (Lex Jurnalica, 2021)
AbstractArticle 2 of Law No. 1 of 1974 concerning Marriage consisted of two paragraphs that contain two qualifications that must be fulfilled for a valid marriage, first, the marriage is carried out based on religious laws, and second, the marriage is registered. In its application, there are two types of application of Article 2, first, marriage that only fulfills the first qualification and second, marriage that fulfills the first and second qualification. In practice, a marriage that only fulfills the first qualification has its own legal consequences for the parties involved, one of which is reflected in Decision No. 1248/PDT.G/2019/PN.DPS where the Plaintiff as the first wife was declared ineligible to file for the cancellation of her husband's polygamous marriage because the marriage registration was carried out after the second marriage. This research aims to explain the legal status of the first wife whose marriage registration is carried out after the second marriage in a polygamous marriage and the legal consequences to the first wife whose marriage registration is carried out after the second marriage in a polygamous marriage. The method used in this research is normative approach. The typology used in this research is descriptive research with secondary data in the form of laws and regulations, books, and scientific works as the main data for analysis. This research found that the first wife whose marriage whose marriage registration was carried out after the second marriage has the legal status as the second wife and the legal consequences for the first wife whose marriage registration was carried out after the second marriage in a polygamous marriage was that the first wife did not obtain the right to give polygamy approval to the next marriage carried out by her husband and the first wife gets a smaller share of the matrimonial property compared to the marriage that has been registered previously.Keywords: marriage, marriage registration, polygamous marriage.AbstrakPasal 2 Undang-Undang No. 1 Tahun 1974 tentang Perkawinan yang terdiri atas dua ayat yang memuat dua unsur yang harus dipenuhi untuk sahnya suatu perkawinan yaitu pertama, perkawinan dilangsungkan berdasarkan hukum agama dan kepercayaan, serta kedua, perkawinan dicatatkan. Dalam penerapannya, timbul dua jenis penerapan atas Pasal 2 tersebut yaitu pertama, perkawinan hanya memenuhi unsur pertama dan kedua, perkawinan memenuhi unsur pertama dan kedua. Dalam praktiknya, perkawinan yang hanya memenuhi unsur pertama menimbulkan akibat hukum tersendiri bagi para pihak yang melakukannya, salah satunya tercermin dalam kasus pada Putusan No. 1248/PDT.G/2019/PN.DPS dimana Penggugat selaku isteri pertama dinyatakan tidak berhak untuk mengajukan pembatalan perkawinan poligami suaminya karena pencatatan perkawinannya dilakukan setelah perkawinan kedua. Penelitian ini bertujuan untuk menjelaskan bagaimana status hukum dari isteri pertama yang pencatatan perkawinannya dilakukan setelah perkawinan kedua dalam perkawinan poligami dan bagaimana akibat hukum bagi isteri pertama yang pencatatan perkawinannya dilakukan setelah perkawinan kedua dalam perkawinan poligami. Penelitian ini menggunakan bentuk penelitian normatif. Tipologi penelitian yang digunakan adalah penelitian deskriptif dengan data sekunder berupa peraturan perundang-undangan, buku, dan karya ilmiah sebagai data utama untuk melakukan analisis. Hasil penelitian yang diperoleh Penulis yaitu isteri pertama yang pencatatan perkawinannya dilakukan setelah pencatatan perkawinan kedua memiliki status hukum sebagai isteri kedua dan akibat hukum terhadap isteri pertama yang pencatatan perkawinan dilakukan setelah perkawinan kedua yaitu isteri pertama menjadi tidak memperoleh hak untuk memberi persetujuan poligami terhadap perkawinan selanjutnya yang dilakukan suaminya dan isteri pertama memperoleh bagian harta bersama yang lebih sedikit dibandingkan dengan perkawinan yang sudah dicatatkan terlebih dahulu.Kata kunci : perkawinan, pencatatan perkawinan, perkawinan poligami.